Communication of Mandiri farming group in increasing the welfare of dry land farmers in Leosama Village, Belu Regency, Indonesia - Biremanoe, Leny Sofia; Pellu, Susana C.L; Oiladang, Chrisistomus S; Meka, Christine E; Jelahut, Felisianus Efrem (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
This paper aims to describe and analyze the role of independent farmer groups in increasing the welfare of dry land farmers in Leosama Village, Belu Regency. The method used in this research is descriptive qualitative. The method used in this research is descriptive qualitative. The resource persons in this research amounted to 15 people who were members of independent farmer groups. Sampling of this research by purposive sampling. The results showed that independent farmer groups in increasing the welfare of its members through close cooperation between them in increasing agricultural production, openness among its members and the existence of kinship ties strengthen the relationship between them. The existence of independent farmer groups plays a very important role in increasing the welfare of its members and overcoming problems together related to the production of agricultural products. From the research data it is recommended that the kinship between the members of the farmer group needs to be maintained so that the existence of the Independent farmer group continues to exist in Leosama Village